Understanding schizophrenia through animal models: the role of environmental stressors - Manojlović, Marina (Archives of Pharmacy, 2024)
Schizophrenia and other related disorders represent a major clinical challenge, with environmental and genetic factors contributing to their occurrence. Animal models are indispensable tools for understanding the complex neurobiological mechanisms underlying psychosis and for developing new therapeutic approaches. This review focuses on the animal models commonly used in schizophrenia research, especially those based on prenatal and postnatal environmental risk factors. Prenatal exposure to infections, such as bacterial lipopolysaccharides (LPS) and viral components such as poly I:C, activates immune responses that lead to long-lasting structural and functional changes in the brain, including hippocampal atrophy and cortical thinning. Postnatal factors such as early life stress, social isolation and drug abuse, particularly cannabis, are also being modelled to investigate their effects on brain development and the onset of psychosis. These models allow controlled manipulation of environmental challenges and provide insights into the aetiology and pathophysiology of the disease. However, the variability of experimental protocols and lack of female representation in many studies underscore the need for more robust and inclusive animal models. Ultimately, these models are crucial for a better understanding of schizophrenia and for testing potential therapeutic interventions.
Keywords: psychosis; prenatal infections; early life stress; social aversion; substance abuse